Status of decontamination methods after using dentin adhesion inhibitors on indirect restorations: An integrative review of 19 publications - Atsushi Mine; Toru Nikaido; Mariko Matsumoto; Tomohiro Takagaki; Masaya Ishida; Shintaro Ban; Azusa Yamanaka; Munechika Takaishi; Masahiro Yumitate; Ryosuke Hagino; Bart Van Meerbeek; Hirofumi Yatani (Elsevier, 2021)
The purpose of this review was to assess the literature regarding the decontamination of resin cement before the luting procedure in order to provide clinicians with a comparative overview of decontamination effects. A total of 19 articles were selected for inclusion in this review. The results indicated that bonding effectiveness is reduced due to residual adhesion inhibitors such as saliva, blood, hemostatic agents, and temporary/provisional cement. Self-etching and self-adhesive systems tend to be more negatively affected by adhesion inhibitors than do etch and rinse systems. Cleaning with an ultrasonic scaler or rotating brush have demonstrated conflicting effects in several studies. Some studies have reported that phosphoric acid has negative effects and recommend mild acid for decontamination. The application of phosphoric acid followed by sodium hypochlorite has been shown to help avoid negative effects. Alumina blasting has been investigated as a mechanical cleaning method in a relatively large number of experiments, most of which have confirmed its effectiveness. An intraoral cleaner containing functional monomers that has become commercially available in recent years is a promising method in clinical practice because it can easily and effectively remove temporary adhesive material. In addition, adhesion inhibitors can be easily removed from resin-coated dentin surfaces.